Institutional and competitive drivers on managers' training and organizational outcomes - Nuria N. Esteban-Lloret; Antonio Aragón-Sánchez; Antonio Carrasco-Hernández (BRQ Business Research Quarterly, 2014)
Studies of the relationship between employee training and outcomes at the company level, in general, do not produce conclusive results. The objective of this paper is to analyze the drivers and outcomes of managers training. Drawing on institutional and economic-rational perspectives, this research explores the reasons why firms train their managers and which outcomes improve in response to training, to explain the ambiguity of the training effect on performance. To achieve the main objective, an empirical study was carried out on 374 Spanish firms. Findings support the idea that managers training is driven by institutional forces, particularly normative and mimetic forces, and to a lesser extent by competitive factors. That implies two different kinds of outcome are achieved by training managers: organizational legitimacy improves as well as organizational performance. While previous studies focus on the rational economic side of the training–outcome relationship, this paper aims to show the importance of the institutional forces in this relationship, looking at drivers and outcomes and so providing further explanations of the effect of training on performance."
Keywords: 650; Managers training; Institutional pressures; Competitive pressures; Organizational legitimacy and organizational performance